Efficacy of Web-Based, Guided Self-help Cognitive Behavioral Therapy-Enhanced for Binge Eating Disorder: Randomized Controlled Trial - Bernou Melisse; Elske van den Berg; Margo de Jonge; Matthijs Blankers; Eric van Furth; Jack Dekker; Edwin de Beurs (JMIR Publications, 2023)
BackgroundOwing to the gap between treatment supply and demand, there are long waiting periods for patients with binge eating disorder, and there is an urgent need to increase their access to specialized treatment. Guided self-help cognitive behavioral therapy-enhanced (CBT-E) may have great advantages for patients if its efficacy can be established. ObjectiveThe aim of this study was to examine the efficacy of guided self-help CBT-E compared with that of a delayed-treatment control condition. MethodsA single-blind 2-arm randomized controlled trial was designed to evaluate guided self-help CBT-E according to an intention-to-treat analysis. A total of 180 patients were randomly assigned to guided self-help CBT-E (n=90, 50%) or the delayed-treatment control condition (n=90, 50%) for which guided self-help CBT-E was provided after the initial 12-week delay. The primary outcome was reduction in binges. The secondary outcome was full recovery at the end of treatment, as measured using the Eating Disorder Examination during the last 4 weeks of treatment. A linear mixed model analysis was performed to compare treatment outcomes at the end of treatment. A second linear mixed model analysis was performed to measure between- and within-group effects for up to 24 weeks of follow-up. The Eating Disorder Examination-Questionnaire and clinical impairment assessment were conducted before and after treatment and during follow-up. In addition, dropout rates were assessed in both conditions. ResultsDuring the last 4 weeks of treatment, objective binges reduced from an average of 19 (SD 16) to 3 (SD 5) binges, and 40% (36/90) showed full recovery in the guided self-help CBT-E group. Between-group effect size (Cohen d) was 1.0 for objective binges. At follow-up, after both groups received treatment, there was no longer a difference between the groups. Of the 180 participants, 142 (78.9%) completed treatment. The overall treatment dropout appeared to be associated with gender, level of education, and number of objective binges at baseline but not with treatment condition. ConclusionsThis is the first study to investigate the efficacy of guided self-help CBT-E. Guided self-help CBT-E appeared to be an efficacious treatment. This study's findings underscore the international guidelines recommending this type of treatment for binge eating disorder. Trial RegistrationNetherlands Trial Registry (NTR) NL7994; https://trialsearch.who.int/Trial2.aspx?TrialID=NL7994 International Registered Report Identifier (IRRID)RR2-10.1186/s12888-020-02604-1